Development and Characterization of SDS Doped Poly(aniline-co-2-isopropylaniline) MWCNT/CuO Nanocomposites for Electrochemical Supercapacitor Application - Singh, Kamal Kant; Sharma, Ashok K. (Asian Journal of Chemistry, 2020)
A novel electroactive nanocomposite material containing aniline-co-2-isopropylaniline (Pani-co), SDS doped poly-Pani-co, copper oxide (CuO), and multiwalled carbon nanotubes (MWCNTs) has been developed by in situ oxidative synthesis technique. The electrochemical execution of synthesised composite as electroactive supercapacitor material was examined through three electrode cell assembly viz. cyclic voltammetry (CV), galvanostatic charge/discharge analysis (GCD) and electrochemical impedance study. Physical and chemical characteristics of synthesized SDS doped Pani-co/MWCNT/CuO nanocomposite were explored via FTIR, TGA, XRD, FESEM and EDX methods. The results confirmed that the existence of metal oxide on MWCNTs enhanced the redox activity of the prepared composite. The maximum specific capacitance obtained in cyclic voltammetric studies was 1473 F/g at sweep rate of 3 mV/s, and the maximum specific capacitance obtained with GCD studies was 1512 F/g at current density of 1A/g in 1M Na2SO4 aqueous solution of with better cycle life.